PP64 Economic Evaluation For Esophageal Cancer Screening In China. (2019) - Li, Yuanyuan; Du, Lingbin; Hu, Xiaoqian; Gu, Shuyan; Zhen, Xuemei; Gu, Yuxuan; Dong, Hengjin
Abstract : Introduction: The aim of the study was to estimate the cost-effectiveness of esophageal cancer (EC) screening compared to non-screening in China. Methods: A Markov model was conducted that followed the history of EC. Screening strategies targeted a population aged 40-69 years, classified into six age groups. Each age group had three cohorts: screening without follow-up, screening with yearly follow-up for low-grade intraepithelial neoplasia (LGIN), and non-screening. Life years (LYs) and quality-adjusted life years (QALYs) presented the effectiveness and utility. The incremental cost-effectiveness ratio (ICER) and incremental cost-utility ratio (ICUR) were evaluating indicators. Eighteen cohorts from 100, 000 hypothetical individuals were used to run the model, until aged 79 years or death. Costs were changed into USD using the purchasing power parity of 3.506 in 2017. The willingness-to-pay was set as three times the gross domestic product per capita (USD 51, 340.6) in 2017. A sensitivity analysis was introduced to assess model robustness. Results: Screening with follow-up compared to non-screening, ages 40-44, 45-49, and 50-54 years, showed cost-effectiveness, with one LY gained costing USD 6, 875.0, USD 9, 204.6, and USD 25, 278.6, respectively. Ages 40-44 and 45-49 years explained cost-utility, with ICURs of USD 6, 709.4/QALY and USD 13, 991.4/QALY, respectively. Screening without follow-up compared to non-screening, ages 40-54 years, addressed cost-effectiveness, with one LY gained costing USD 6, 934.8, USD 9, 760.0, and USD 35, 126.0 in ages 40-44, 45-49, and 50-54 years, respectively; the 40-44 years age group demonstrated cost-utility with an ICUR of USD 8, 512.3/QALY. Screening with follow-up compared to screening without follow-up, all ages, explained cost-effectiveness and cost-utility. The probabilistic sensitivity analysis supported the outcome of the base cohort analysis. Conclusions: Compared to non-screening, screening with follow-up targeting ages 40-54 years was highly recommended with the ICER as the evaluated indicator, whereas it targeting ages 40-49 years was suggested with the ICUR as indicator.